The best poems of the English language : from Chaucer through Frost - Bloom, Harold (HarperCollins, 2004)
Presents an anthology of British and American poetry chosen by editor Harold Bloom on the basis of aesthetic splendor, intellectual power, and wisdom; featuring selections drawn from throughout six centuries, from Chaucer to poets whose births predate 1900.